Complement Blockade in Recipients Prevents Delayed Graft Function and Delays Antibody-mediated Rejection in a Nonhuman Primate Model of Kidney Transplantation. Issue 1 (13th December 2021) - Eerhart, Michael J.; Reyes, Jose A.; Blanton, Casi L.; Danobeitia, Juan S.; Chlebeck, Peter J.; Zitur, Laura J.; Springer, Megan; Polyak, Erzsebet; Coonen, Jennifer; Capuano, Saverio; D'Alessandro, Anthony M.; Torrealba, Jose; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Complement activation in kidney transplantation is implicated in the pathogenesis of delayed graft function (DGF). This study evaluated the therapeutic efficacy of high-dose recombinant human C1 esterase inhibitor (rhC1INH) to prevent DGF in a nonhuman primate model of kidney transplantation after brain death and prolonged cold ischemia. Methods: Brain death donors underwent 20 h of conventional management. Procured kidneys were stored on ice for 44–48 h, then transplanted into ABO-compatible major histocompatibility complex-mismatched recipients. Recipients were treated with vehicle (n = 5) or rhC1INH 500 U/kg plus heparin 40 U/kg (n = 8) before reperfusion, 12 h, and 24 h posttransplant. Recipients were followed up for 120 d. Results: Of vehicle-treated recipients, 80% (4 of 5) developed DGF versus 12.5% (1 of 8) rhC1INH-treated recipients ( P = 0.015). rhC1INH-treated recipients had faster creatinine recovery, superior urinary output, and reduced urinary neutrophil gelatinase-associated lipocalin and tissue inhibitor of metalloproteinases 2-insulin-like growth factor-binding protein 7 throughout the first week, indicating reduced allograft injury. Treated recipients presented lower postreperfusion plasma interleukin (IL)-6, IL-8, tumor necrosis factor-alpha, and IL-18, lower day 4 monocyte chemoattractant protein 1, and trended toward lower C5. Treated recipients exhibited less C3b/C5b-9 deposition on day 7 biopsies. rhC1INH-treated animals also trended toward prolonged mediated rejection-free survival. Conclusions: Our results recommend high-dose C1INH complement blockade in transplant recipients as an effective strategy to reduce kidney injury and inflammation, prevent DGF, delay antibody-mediated rejection development, and improve transplant outcomes.